Fabrication and characterization of fibroin solution and nanoparticle from silk fibers of Bombyx mori. (4th May 2017) - Kumar, Sandeep; Singh, Sandeep Kumar
ABSTRACT: The present investigation aims to study the effect of degumming time on the structural property of silk fiber obtained by silk cocoons of Bombyx mori, followed by preparation of the regenerated silk fibroin (RSF) solution which can be subsequently molded into silk nanoparticles. Silk fibers degummed with different media at different time intervals were investigated for the degumming loss and were characterized using Ffourier transform infrared (FTIR), differential scanning calorimetry (DSC), x-ray diffraction (XRD), and scanning electron microscopy (SEM). Maximum degumming was observed when the fibers were treated with sodium carbonate for 60 min. SEM and atomic force microscopy (AFM) images of RSF solution showed aggregation of silk globules resulting in formation of solvated macrochains and giving it an appearance of island-like morphology. Blank silk nanoparticles prepared from the RSF solution showed a smooth and spherical surface devoid of any adhesion using SEM, AFM, and transmission electron microscopy (TEM). The prepared silk nanoparticles may further be explored for loading drug entities and targeting.